RHEUMATOID ARTHRITIS AND CARDIOVASCULAR RISK: PERSPECTIVES OF TREATMENT WITH STATINS - D. A. Anichkov; N. A. Shostak (Рациональная фармакотерапия в кардиологии)
The cardiovascular risk factors in patients with rheumatoid arthritis (RA) are reviewed. The perspectives of treatments with statins in RA are given. Results of clinical trials on statin effects on the inflammatory disease activity and endothelial function in patients with RA are summarized.